2018
DOI: 10.1002/mp.12992
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of spectral and intensity changes with measurement geometry in various light guides used in scintillation dosimetry

Abstract: The insignificant change in the CLR with delivered dose indicates that a single CLR value over the investigated dose range is sufficient for accurate Čerenkov subtraction. Variations in the stem-effect spectrum shape can occur with changes in irradiation geometry. The magnitude of the changes are governed by the fiber construction and the optical properties of the fiber. The observed spectral shape changes can be explained by a combination of variations in optical path length through the fiber and the fiber fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…This approach is very effective if the measurements fall within these ranges of the calibration conditions 29,48–50 . However, it has been reported that the calibration conditions affect the accuracy of stem signal elimination 30,32 . Furthermore, the spectrum during measurement may differ from that at the time of calibration depending on the bending of the optical fiber 32 and temperature, and these factors may also cause errors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This approach is very effective if the measurements fall within these ranges of the calibration conditions 29,48–50 . However, it has been reported that the calibration conditions affect the accuracy of stem signal elimination 30,32 . Furthermore, the spectrum during measurement may differ from that at the time of calibration depending on the bending of the optical fiber 32 and temperature, and these factors may also cause errors.…”
Section: Discussionmentioning
confidence: 99%
“…29,[48][49][50] However, it has been reported that the calibration conditions affect the accuracy of stem signal elimination. 30,32 Furthermore, the spectrum during measurement may differ from that at the time of calibration depending on the bending of the optical fiber 32 and temperature, and these factors may also cause errors. Guillot et al 30 noted that optical fiber attenuation could be an additional source of error.…”
Section: A Developed Dosimeter Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The main caveat of these detectors, as many have previously highlighted, 1,3–5,8–12 is that they are susceptible to an unwanted background, or stem‐effect, signal that can degrade the accuracy of these detectors if it is not properly removed. The stem‐effect is composed of Čerenkov radiation generated in the light guide and sensitive detector volume and fluorescence generated in the light guide.…”
Section: Introductionmentioning
confidence: 99%